SELECTIVE SEROTONIN REUPTAKE INHIBITORS AND THE RISK OF TYPE 2 DIABETES MELLITUS - De Long, Nicole (My University, 2016)
Major Depressive Disorder (MDD) is a wide spread psychiatric disorder which affects more than 350 million people worldwide. Of the current available treatments, Selective Serotonin Reuptake Inhibitors (SSRIs) are the most commonly prescribed. Long-term SSRI use has been associated with the onset of Type 2 Diabetes (T2DM) in adults. T2DM is driven by beta cell dysfunction and hence we wanted to investigate the mechanism(s) by which SSRIs were causing beta cell demise. We have found that fluoxetine, more commonly known as Prozac®, does in fact disturb beta cell function by inducing mitochondrial dysfunction and thereby oxidative damage. Interestingly, women are twice as likely to experience MDD, and this risk peaks during childbearing years. As a result, up to 1 in 10 pregnancies are complicated with SSRIs. This is an astonishing number considering the long-term effects of these drugs on the children are unknown. Within this thesis I report for the first time, the long-term metabolic outcomes of fetal and neonatal exposure to SSRIs in a rodent model. We have found that antenatal exposure to fluoxetine results in altered glucose homeostasis and impaired insulin sensitivity in the adult offspring. Furthermore we have shown that epigenetic modifications may be implicated in the increased incidence of fatty liver in these offspring. These findings demonstrate a predisposition to the development of obesity and T2DM into adulthood. These findings are novel and have clinical importance with respect to mothers taking these drugs during pregnancy. Within this thesis we are not advising mothers with depression to discontinue medication. We are merely exploring the risks in a rodent model while acknowledging that a significant amount of research is required before applying theses results to the human population.
SSRIs and the risk of T2DM